Improving Technical Vocational Education and Training in the Kurdistan Region-Iraq - Constant, Louay (RAND Corporation, 2014)
The Kurdistan Region-Iraq (KRI) is enjoying rapid economic growth, creating many new jobs that require a solid education and technical skills. The Kurdistan Regional Government has expanded opportunities for post-secondary technical and university education, secondary-level vocational education has lagged. Even though the region is establishing new vocational education centers, more work is needed to address current shortcomings and future needs.